Diverse Long-Term Effects of Childhood Exposure to Intimate Partner Violence: Development of Externalizing Behaviors in Males and Females - Weir, Henriikka (Journal of interpersonal violence, 2021)
Using data from all three waves of the Project on Human Development in Chicago Neighborhoods (PHDCN) longitudinal cohort study, this article examined the long-term effects of intimate partner violence (IPV) exposure during childhood and early adolescence on subsequent externalizing behaviors (i.e., delinquency, violence, and drug offenses). A propensity score matching (PSM) was employed to match a group of individuals reporting childhood/adolescence IPV exposure to those not exposed to IPV on key variables. Longitudinal latent class analyses (LLCA) were then utilized to estimate the longitudinal developmental trajectories of externalizing behaviors separately for the IPV- and non-IPV-exposed males and females and compared with each other. PSM revealed that there were small but significant differences in mean levels of externalizing behaviors between IPV-exposed and non-IPV-exposed youth at Waves 2 and 3. Furthermore, LLCA indicated that there were three distinct developmental trajectories of externalizing behaviors among the IPV-exposed males but four distinct developmental trajectories of externalizing behaviors among the IPV-exposed females, non-IPV-exposed males, and non-IPV-exposed females. Overall, the IPV-exposed males had the largest number of life-course-persistent offenders as well as adolescents who started their offending at a very early age but rapidly declined by the end of the study period. However, the non-IPV-exposed males’, albeit smaller, life-course-persistent group displayed by far the highest levels of externalizing behaviors of the entire sample. Females in the present study were largely similar to each other in the development of externalizing behaviors, regardless of IPV exposure. Policy implications are discussed.